Ocena ekonomicznej efektywności gospodarki leśnej prowadzonej przez Leśny Zakład Doświadczalny w Krynicy - Kożuch, Anna; Ryś, Magdalena (Leśne Prace Badawcze, 2016)
The Forest Experimental Station (FES) in Krynica is a unit specialized in teaching activities. However, it also fulfils other educational, ecological and social functions. Additionally, as the FES in Krynica operates on the free market and needs to be competitive, primarily with respect to the raw timber prizes, it is also a forest management unit that can be subjected to economic evaluation. The aim of this study was to analyze the income, costs and overall financial outcome of the FES in Krynica for the years of 2008–2012. A financial analysis, using indicators of financial liquidity, profitability, economic activity and liabilities, was also carried out to evaluate the economic effectiveness and efficiency of the forest management unit’s operation. The data was obtained from financial documents, particularly balance sheets, as well as profit and loss accounts. In the years of 2008–2012, mean income and costs of the FES in Krynica amounted to 7 121.1 thous. PLN/year and 6 478.2 thous. PLN/year, respectively. The net financial outcome was positive and amounted to a mean of 628.8 thous. PLN/year. The proportionof the sale income compared to the total income from all activities carried out by the unit increased from 93% to 96%. This included income from the sale of products, goods and materials, which increased by 57% mainly due to an increase in the income from timber sales (ca. 83%). Costs incurred by the unit increased as well, being 40% higher in 2012 than in 2008, while the cost level indicator decreased by ca. 8%. In the examined time period, the economic effectiveness and efficiency of the unit’s operation improved, as evidenced by the increasing profits and the values of the profitability indicators. Results obtained in the comprehensive analysis of the financial situation in the FES in Krynica provide a basis for the evaluation of economic processes and for appropriate decision making concerning wealth management and the direction of future development. In the evaluation of the economic and financial activity of the FES in Krynica, the increase inprofitability in the analysed time period, as concluded from the indicator of turnover profitability, was particularly noteworthy. The financial indicator values greatly exceed reference values only on the level of financial liquidity. The liability indicators served as evidence of obvious financial independence of the FES in Krynica.